Baby steps: The expanding financial base of local government in Ireland - Considine John; Reidy Theresa (Administration, 2015)
There are two essential elements to this paper. In the first instance, we explore the specific details of revenue and expenditure trends for local authorities over the last decade. The analysis is framed against a longer-term political context of forty years which focuses especially on the weakness of local government in Ireland. Despite an official narrative of financial overdependence on central government, the comparative examination of budgetary records of local authorities reveals considerable diversity in both the revenue and expenditure patterns of authorities across the state. While some authorities are heavily reliant on central government funding, others have a much stronger base of local funding, and indeed the financial crisis since 2008 may have increased these differences. The second dimension to the research is an exploration of the impact of the great recession from 2008 on local government finance in Ireland. Using a framework of new institutionalism, we identify the crisis as another critical moment for local government. We consider the political, economic and administrative variables which have brought local government to a financial crossroads, and we explore the potential for long-lasting financial change in local government, as well as speculating on the nature and outcome of that change.